When Potential Allies and Targets Do (and Do Not) Confront Anti-Asian Prejudice: Reactions to Blatant and Subtle Prejudice During the COVID-19 Pandemic - Ratcliff, Jennifer J. (Journal of interpersonal violence, 2023)
Anti-Asian xenophobia has exploded during the COVID-19 pandemic, after U.S. political leaders promoted anti-Asian rhetoric from its start. Confronting prejudice interrupts future perpetration of such prejudice, but confronting prejudice can only occur to the extent actions are first attributed to prejudice. Bystanders may attribute less prejudice to speech about the “Chinese Virus” than to more blatant stereotype expression, for example, and therefore be less vehement in their confrontations. Across two studies, we examined the impact of anti-Asian prejudice type (blatant, subtle, or no prejudice) and bystander race/ethnicity (White or Asian American/Pacific Islander [AAPI]), on prejudice attribution, willingness to confront, actual confrontation, and confrontation vehemence. In the context of a hiring manager justifying rejection of a Chinese applicant, we predicted that blatant prejudice would be detected and confronted most willingly, and subtle prejudice more willingly than no prejudice, and that prejudice detection would mediate the relationship between prejudice type and willingness to confront. Further, we expected AAPI bystanders to detect anti-Asian prejudice more readily than White bystanders, but to confront at lower rates, with actual confrontations being more vehement following blatant (relative to subtle or no) prejudice. Analyses were conducted using SPSS 27 and the PROCESS v4.1 macro, controlling for potential confounds such as political orientation and individual-level prejudice (expressed or perceived). Results of both studies (n = 142 [Study 1], n = 274 [Study 2]) supported hypotheses, except in Study 1 bystanders exposed to subtle prejudice were no more willing to confront than no-prejudice controls. Results of exploratory analyses indicated that attribution to prejudice was the primary obstacle to confrontation following subtle prejudice, whereas action taking was the primary obstacle following blatant prejudice. This research underscores the need for interventions to increase detection of all forms of anti-Asian prejudice and to provide would-be confronters with effective confrontation tools.